Globalized e-learning cultural challenges - Edmundson, Andrea 1955- (Gale virtual reference library, 2007)
"This book's purpose is to inform educators and instructional designers of issues and cultural misunderstandings that could hinder the effective transfer of knowledge when e-learning is exported to other cultures. Addressing these cultural challenges will enhance the effectiveness of e-learning, thereby supporting the societal benefits of increased access to education at a global level."--Provided by publisher.